Autoreactive T cell profiles are altered following allogeneic islet transplantation with alemtuzumab induction and re‐emerging phenotype is associated with graft function. Issue 3 (19th September 2020) - Sabbah, Shereen; Liew, Aaron; Brooks, Augustin M.; Kundu, Rhiannon; Reading, James L.; Flatt, Anneliese; Counter, Claire; Choudhary, Pratik; Forbes, Shareen; Rosenthal, Miranda J.; Rutter, Martin K.; Cairns, Stephanie; et al.
Abstract: Islet transplantation is an effective therapy for life‐threatening hypoglycemia, but graft function gradually declines over time in many recipients. We characterized islet‐specific T cells in recipients within an islet transplant program favoring alemtuzumab (ATZ) lymphodepleting induction and examined associations with graft function. Fifty‐eight recipients were studied: 23 pretransplant and 40 posttransplant (including 5 with pretransplant phenotyping). The proportion with islet‐specific T cell responses was not significantly different over time (pre‐Tx: 59%; 1–6 m posttransplant: 38%; 7–12 m: 44%; 13–24 m: 47%; and >24 m: 45%). However, phenotype shifted significantly, with IFN‐γ–dominated response in the pretransplant group replaced by IL‐10–dominated response in the 1–6 m posttransplant group, reverting to predominantly IFN‐γ–oriented response in the >24 m group. Clustering analysis of posttransplant responses revealed two main agglomerations, characterized by IFN‐γ and IL‐10 phenotypes, respectively. IL‐10–oriented posttransplant response was associated with relatively low graft function. Recipients within the IL‐10 + cluster had a significant decline in C‐peptide levels in the period preceding the IL‐10 response, but stable graft function following the response. In contrast, an IFN‐γ response was associated with subsequently decreased C‐peptide. Islet transplantation favoring ATZ induction is associated with an initial altered islet‐specific T cell phenotype but reversion toward pretransplant profiles over time. Posttransplant autoreactive T cell phenotype may be a predictor of subsequent graft function. Abstract : The phenotype of islet‐specific T cell responses evolves after islet transplantation and the alterations may predict subsequent graft function.